2013
DOI: 10.1088/0957-4484/24/45/455204
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free molecular junctions on ITO via amino-silane binding—towards optoelectronic molecular junctions

Abstract: Light control over currents in molecular junctions is desirable as a non-contact input with high spectral and spatial resolution provided by the photonic input and the molecular electronics element, respectively. Expanding the study of molecular junctions to non-metallic transparent substrates, such as indium tin oxide (ITO), is vital for the observation of molecular optoelectronic effects. Non-metallic electrodes are expected to decrease the probability of quenching of molecular photo-excited states, light-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The most critical step in the junction fabrication process is often considered to be step iii as the relative fragile molecular structure may be altered or damaged during the fabrication of the top electrode. [2,3,6] Therefore, large-area molecular junctions have been fabricated with protective layers (PLs) on top of the monolayer (such as, graphene [92,[97][98][99] and derivatives thereof, [100] electron-beam deposited carbon (eC), [101,102] carbon paint, [103] GaO x in EGaIn junctions, [104] or conductive polymers [105][106][107][108] ), which, in principle, provide stability and protect the monolayer during fabrication of the top-electrode. In reality the situation is more complicated as the PL adds complexity since additional SAM-PL and PL-top electrode interfaces have to be considered.…”
Section: Large-area Molecular Junctionsmentioning
confidence: 99%
“…The most critical step in the junction fabrication process is often considered to be step iii as the relative fragile molecular structure may be altered or damaged during the fabrication of the top electrode. [2,3,6] Therefore, large-area molecular junctions have been fabricated with protective layers (PLs) on top of the monolayer (such as, graphene [92,[97][98][99] and derivatives thereof, [100] electron-beam deposited carbon (eC), [101,102] carbon paint, [103] GaO x in EGaIn junctions, [104] or conductive polymers [105][106][107][108] ), which, in principle, provide stability and protect the monolayer during fabrication of the top-electrode. In reality the situation is more complicated as the PL adds complexity since additional SAM-PL and PL-top electrode interfaces have to be considered.…”
Section: Large-area Molecular Junctionsmentioning
confidence: 99%
“…[ 18,22 ] Finally, top contacts were evaporated through a shadow mask. In principle, this last patterning step can also be done with CMOS-compatible lithography, [ 10,12,13 ] but with our facility a shadow-mask was more convenient. As poor adhesion between the evaporated metal and the insulator's inner wall could cause dis-connects at the top rim, [ 13 ] we used a rather thick Pb layer, to fi ll-up the wells (Figure 1 a.IV).…”
Section: Full Papersmentioning
confidence: 99%
“…Defects in rectifying junctions can increase the conductance by orders of magnitudes, compared to a defect‐free junction and, thus, their relative contribution is not proportional to their fractional area and is expected to increase for smaller junctions . Leakage through surrounding insulators scales with the perimeter length and is, therefore, also more pronounced, the smaller the contact area is. Thus, one way to test for transport artifacts is to compare the current densities across junctions of varying contact areas .…”
Section: Introductionmentioning
confidence: 99%
“…With the dramatic scaling of silicon devices to the sub-20 nm length scale, it is becoming critical to probe transport properties of complex silicon-based nanoscale structures, such as silicon clusters, nanowires and silicene 2D layers. 1 4 Efforts in molecular electronics have demonstrated the use of silicon surfaces as electrodes 5 9 and amino-silanes as chemical binding groups to the electrodes. 10 , 11 Moreover, investigation on cyclohexasilane 12 has shown that conformations affect the molecule's electronic structure and another study on [2,2,2]bicyclic carbosilane systems 13 has suggested that different disilanylene bridges in the cage compounds do not act as parallel resistors.…”
Section: Introductionmentioning
confidence: 99%